Anaplastic lymphoma kinase–positive anaplastic large cell lymphoma presenting as diffuse pulmonary infiltrates. Issue 10 (3rd July 2020) - Sato, Shuku; Tamai, Yotaro
Abstract: Anaplastic large cell lymphoma has a characteristic sinusoidal growth pattern that presents as pulmonary lymphangitic involvement causing respiratory distress. Recognition and prompt treatment of this entity can result in dramatic response to therapy. Abstract : Anaplastic large cell lymphoma has a characteristic sinusoidal growth pattern that presents as pulmonary lymphangitic involvement causing respiratory distress. Recognition and prompt treatment of this entity can result in dramatic response to therapy.